THE EFFECTIVENESS OF USING ANIMATED FABLE VIDEOS IN TEACHING NARRATIVE TEXT WRITING - Irdawati, Riska; Marbun, Rismaya; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This thesis discusses about the animated fable video which is used as teaching media in teaching narrative text writing. The problem of this research is: How effective is the use of animated fable video in teaching narrative text writing of tenth grade students of SMA Mujahidin Pontianak? The design of this research is a pre-experimental study.The sample of the research is the X MIA 2 class of SMA Mujahidin Pontianak which included 32 students. The researcher used t-table to measure the significance of teaching by using animated fable video in teaching narrative text writing and the result of t-value 9.28 is higher than t-table 2.000 on the level significance 5%. The researcher also used effect size (ES) to analyze the effectiveness of using animated fable video in teaching narrative text writing and the result of the ES is 1.58 is categorized â€œHighâ€. Based on the result the use of the animated fable video in teaching narrative text writing to the tenth grade students of SMA Mujahidin Pontianak is highly effective. Key words : Animated fable video, narrative writing Â Abstrak: Skripsi ini membahas tentang video animasi hewan yang digunakan sebagai media dalam mengajar Â penulisan teks naratif. Permasalahan dalam penelitian ini adalah: Bagaimana keefektifitasan dari penggunaan video animasi hewan dalam mengajar penulisan teks naratif pada siswa kelas sepuluh SMA Mujahidin Pontianak? Desain dari penelitian ini adalah pre-experimental. Sampel penelitian adalah kelas X MIA 2 SMA Mujahidin Pontianak yang terdiri dari 32 siswa. Peneliti menggunakan t-tabel 2.000 pada level signifikan 5%. Peneliti juga menggunakan effect size (ES) untuk menganalisa keefektifitasan penggunaan video animasi hewan dalam mengajar penulisan teks naratif dan hasil dari effect size (ES) adalah 1.58 sehingga dapat dikategorikan â€œTinggiâ€. Berdasarkan hasil tersebut, penggunaan video animasi hewan dalam mengajar penulisan teks naratif pada kelas sepuluh SMA Mujahidin Pontianak dikategorikan memiliki level keefektifitasan yang tinggi. Kata kunci : Video animasi hewan, penulisan teks naratif